Navigating the nexus: how climate change risk perception and economic dependence influence local support for sustainable tourism - Karakuş, Yusuf; Onat, Gökhan; Balıkçıoğlu Dedeoğlu, Sevgi (Revista Rosa dos Ventos - Turismo e Hospitalidade, 2026)
This study examines the mediating role of economic dependence in the influence of local people's climate change risk perception on their support for sustainable tourism development in a climate-sensitive and economically tourism-dependent region. Integrating Protection Motivation Theory and Social Exchange Theory the research analyzes how threat perceptions and economic interests shape sustainable tourism development attitudes. Structural Equation Modeling was used with data collected from 397 local residents in Rize, Türkiye. The findings show that climate change risk perception positively influences both economic dependence and support for sustainable tourism development, and economic dependence positively influences support for sustainable tourism development. Most importantly, economic dependence was found to play a significant partial mediating role in the relationship between climate change risk perception and sustainable tourism development support, i.e., the effect of climate change risk perception on sustainable tourism development is partially mediated by perceived economic security. The study contributes to theoretical understanding by identifying economic dependence as a key mechanism in the protection motivation theory -social exchange theory interaction and provides policy recommendations that balance climate risk communication with the economic benefits of sustainable tourism development. This is particularly important for regions facing dual pressures of climate change and economic interdependence.